1998
DOI: 10.1038/sj.sc.3100516
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of serotonin during rest and during exercise in paraplegic patients

Abstract: The purpose of this study was to evaluate the serum level of serotonin (5-HT) during rest and response to exercise in subjects with spinal cord injury (SCI) with di erent levels of physical activity. Twenty-®ve male subjects with traumatic paraplegia, the neurological levels being between T1 and T12, volunteered for the study. They were divided into two groups matched for age, weight and time since injury, according to the level of physical activity: 14 inactive and 11 subjects regularly involved in sports act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…However, human studies that have examined the contribution of the ␤-endorphins to PEH by blocking the system with naloxone have elicited contradictory results. 7,10 The concentrations of peripherally circulating 5-HT in the present study were considerably lower than those found in other studies (eg, Steinberg et al 19 ). We attribute this to our control to 5-HT release from platelets.…”
Section: Discussioncontrasting
confidence: 84%
“…However, human studies that have examined the contribution of the ␤-endorphins to PEH by blocking the system with naloxone have elicited contradictory results. 7,10 The concentrations of peripherally circulating 5-HT in the present study were considerably lower than those found in other studies (eg, Steinberg et al 19 ). We attribute this to our control to 5-HT release from platelets.…”
Section: Discussioncontrasting
confidence: 84%
“…This neuropharmacological result could be due to attenuation of the elevation in a TRP:BCAAs ratio by administration of BCCAs (Burke, 2001;Nemet and Eliakim, 2007). It is well documented that prolonged physical exercise increases serotonin levels (Steinberg et al, 1998) rather than intermittent exercise (Eichelberger and Bilodeau, 2007). This is mainly due to slower oxidation of BCAAs during the recovery period (Nemet and Eliakim, 2007) and subsequently, it prevents an increase of plasma TRP concentration (Steinberg et al, 1998).…”
Section: Biochemical Variablesmentioning
confidence: 99%
“…It is well documented that prolonged physical exercise increases serotonin levels (Steinberg et al, 1998) rather than intermittent exercise (Eichelberger and Bilodeau, 2007). This is mainly due to slower oxidation of BCAAs during the recovery period (Nemet and Eliakim, 2007) and subsequently, it prevents an increase of plasma TRP concentration (Steinberg et al, 1998). However, in our study the plasma serotonin level was higher in both trials compared to baseline value (165.7 ± 13.8 ng/ml; Table 1) and normal range (68-232 ng/ml), indicating that during exercise the participants reached the point of 'central fatigue', due to the serotonergic system.…”
Section: Biochemical Variablesmentioning
confidence: 99%
“…The mechanism for this inhibition of sympathetic outflow is unknown. Interestingly, serotonin has been found to increase during exercise in brain tissue of rats 98 and in blood samples of humans 99 and may be involved in PEH.…”
Section: Opioids And/or Serotoninmentioning
confidence: 99%